Contested Terrain : Reflections with Afghan Women Leaders - Kitch, Sally (Book collections on Project MUSE., 2014)
"Contending with the complex dynamics of a society both undergoing and resisting change, Basel and Afghani speak candidly - and critically - of international intervention, the oppression of women, patriarchal Afghan culture, and the climate among Afghan women that limits change ... Strongly rooted in feminist theory and supported by interdisciplinary historical and geopolitical analysis, Contested Terrain sheds new light on the struggle against the powerful forces that affect Afghan women's education, health, political participation, livelihoods, and quality of life."--Back cover